Assisted Coral Reproduction in the Dominican Republic: A Successful Story to Replicate in the Caribbean - Sellares-Blasco, Rita I.; Villalpando, Maria F.; Guendulain-García, Sergio D.; Croquer, Aldo (Frontiers in Marine Science, 2021)
Assisted fertilization, larval rearing and recruit propagation success in significant ecological scales, largely depend on scaling up and replicating these efforts in as many regions as possible. The Dominican Foundation for Marine Studies (FUNDEMAR) has become a pioneer of these efforts in the Dominican Republic, being the first institution to successfully implement sexual reproduction techniques in the country and establishing the first mobile larvae culturing facility. Here we share four main components behind the success of FUNDEMAR’s coral assisted fertilization program: (1) the design and construction of the first Coral Assisted Reproduction Laboratory in the country (2) the incorporation of novel techniques in alliance with local and international organizations (3) a self-sustainable program (4) science-based knowledge to improve reproduction, culture, restoration and monitoring. Two years after program implementation, FUNDEMAR has successfully produced an annual regional coral spawning prediction calendar, cultured seven coral species, and out-planted over 4,600 tiles with more than 233,000 coral sexual recruits in approximately 1,880 m2 reef areas. Here, we provide a detailed description of a fully functional assisted coral reproduction program, including the lessons learned during its implementation as well as a series of specific solutions. We hope this work will help and inspire other countries and small institutions to replicate FUNDEMAR´s coral assisted fertilization program and contribute to the expansion of sexual coral restoration efforts in the Caribbean.